Truly low temperature sintering of printed copper ink using formic acid - Hermerschmidt, Felix; Burmeister, David; Ligorio, Giovanni; Pozov, Sergey M.; Ward, Richard; Choulis, Stelios A.; List-Kratochvil, Emil J. W. (My University, 2018)
Low cost electronics are targeted by using solution-based, upscalable printing technologies, focusing on cost-efficient materials and additive processes to yield conducting structures with minimal material consumption. Copper nanoparticles (CuNPs) can form the basis for such processes. However, due to the susceptibility of Cu to oxidation, the usual postdeposition treatment methods include expensive and instrumentally elaborate flash lamp and laser sintering approaches. A simple, truly low temperature (130 °C), easy to scale process is reported by using formic acid to sinter structures that are inkjet-printed using an industrial scale CuNP ink. Electrical conductivity of up to 16% bulk Cu is observed when sintering is carried out at 130 °C and more than 25% bulk Cu conductivity is observed above 150 °C. Four-point measurements and photoemission spectroscopy detail the formation of a conducting Cu film under the influence of formic acid. Adhesion and bending tests confirm the stability of the thin (<500 nm) printed structures to up to 2% tensile strain. The developed sintering process is specifically targeted for flexible low cost and low temperature compatible plastic substrates such as polyethylene terephthalate. The results underline the suitability of the inkjet process for upscalable Cu electrode production in electronic devices.
Keywords: Copper nanoparticle ink; High conductivity; Inkjet-printed electronics; Low cost flexible substrates; Low temperature sintering